Corporate finance, financial development, and growth - Bebczuk, Ricardo Nestor (2001)
A great deal of empirical work has convincingly shown that there is a positive association between financial development and economic growth, and some recent work has even provided evidence that the former causes the latter. What is less clear is the identification of the actual transmission channel. This paper is an attempt in this direction, with particular emphasis placed on the role of the financial system in alleviating informational asymmetries. While research in this field has highlighted the benefits of well developed financial systems, the observation that internal funds (retained earnings plus depreciation) constitute by far the main source of funds of the corporate sector has not gained any attention. We believe that the informational frictions that lie behind this phenomenon may be part of the missing empirical link between financial system and growth. In particular, we will show that such frictions create a financing constraint that reduces investment and growth.